2022
DOI: 10.3389/fphys.2022.878955
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Long-Lasting Static Stretching on Maximal Strength, Muscle Thickness and Flexibility

Abstract: Background: In animal studies long-term stretching interventions up to several hours per day have shown large increases in muscle mass as well as maximal strength. The aim of this study was to investigate the effects of a long-term stretching on maximal strength, muscle cross sectional area (MCSA) and range of motion (ROM) in humans.Methods: 52 subjects were divided into an Intervention group (IG, n = 27) and a control group (CG, n = 25). IG stretched the plantar flexors for one hour per day for six weeks usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(106 citation statements)
references
References 79 publications
8
94
3
1
Order By: Relevance
“…Previous research on daily long-lasting static stretching showed significant increases in MSt measured in the extended knee joint, comparable to those in the present study. Since Warneke et al [ 31 ] showed significant hypertrophy in the plantar flexors due to long-lasting stretching intervention, which could possibly be attributed to stretch-induced mechanical tension, leading to hypertrophy and MSt increases, a general transferability of the effects observed in animal studies to humans could be hypothesized. The hypothesis of mechanical-induced structural changes are confirmed by the results of a variety of animal studies [ 40 ], showing significant increases in muscle mass, the muscle cross-sectional area and the fiber cross-sectional area due to chronic stretching interventions: “It is Stretch that causes the Hypertrophy of Muscle” ([ 41 ] p. 93).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research on daily long-lasting static stretching showed significant increases in MSt measured in the extended knee joint, comparable to those in the present study. Since Warneke et al [ 31 ] showed significant hypertrophy in the plantar flexors due to long-lasting stretching intervention, which could possibly be attributed to stretch-induced mechanical tension, leading to hypertrophy and MSt increases, a general transferability of the effects observed in animal studies to humans could be hypothesized. The hypothesis of mechanical-induced structural changes are confirmed by the results of a variety of animal studies [ 40 ], showing significant increases in muscle mass, the muscle cross-sectional area and the fiber cross-sectional area due to chronic stretching interventions: “It is Stretch that causes the Hypertrophy of Muscle” ([ 41 ] p. 93).…”
Section: Discussionmentioning
confidence: 99%
“…However, the aim of this study was not to investigate gender-related differences regarding stretching-induced improvements in MSt. Since it is well accepted that stretch training could lead to increases in flexibility in general [ 48 , 49 ], and Warneke et al [ 31 ] showed significant improvements in flexibility due to a similar stretching intervention, we did not examine the influence of stretching on flexibility in this study. It was not possible to include equal sample sizes in the study as not all participants were willing to join the two-hour stretching group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations